Islamic Aqidah Learning Management to Explore the Potential of Madrasah Students - Suprapti, Suprapti; Ilmiyah, Najimatul; Latifah, Latifah; Handayani, Noor Fazariah (Budapest International Research and Critics University, 2022)
The main objective of this research is to describe the planning, implementation, evaluation of Islamic Aqidah learning as well as obstacles and solutions for implementing Islamic Aqidah learning at Madrasahs in South Kalimantan. The research method used is a descriptive qualitative approach and the type of research is multi-site. Data collection techniques using interview and observation techniques. The results showed that the management of Islamic Aqidah learning in Madrasahs in South Kalimantan included the stages, namely planning, implementation, and assessment of learning outcomes (evaluation), as well as factors that became obstacles and solutions to the implementation of Islamic Aqidah learning. The potential of students explored in Islamic Aqidah learning is the basic potential as human beings such as the potential for self-existence, compassion, religion, and intellectuality.